الأبعاد الدلالية والتداولية للنص المصاحب " في موطأ الإمام مالك " - الدكتور : رابح بومعزة, غصاب منصور الصقر (Revues faculté des lettres et des langues, 2016)
تهدف هذه الدراسة إلى دراسة الأبعاد الدلالية والتداولية للنص المصاحب، في موطأ الإمام مالك بن أنس من خلال نماذج مختارة اختيرت لذلك.             قامت هذه الدراسة على فكرة أساسية مفادها أنَّ الدلالة والتداول في موطأ الإمام مالك لا تتوقف عند حدود النص اللساني، بل تتعداه إلى النص المصاحب الذي يشمل إشارات أعضاء الجسم الإنساني مثل الوجه واليد والعين والرأس والرجل والفم والأذن. فدلالات هذه الأعضاء تمثل رافدًا مهمًا من روافد الإبانة والتوضيح، عن المعاني، ومقاصد المتكلم في عملية التواصل الإنساني؛ فتؤثر في سلوكاتهم بشكل كبير، وتترجِم كل ما يدور في خلجات أنفسهم الداخلية عبر أعضاء الجسم الخارجية.             وقد كشفت الدراسة - من خلال تتبع النصوص المصاحبة - عن أهمية هذه النصوص في توضيح المعاني الدقيقة؛ لما تضمَّنته من دلالات إشارية جسمية. This study aims to examine the dimensions of semantres and Pragmaticals pragmatris a text in Muwatta Imam Malik bin Anas through selected models chosen. This study was based on the idea that the fundamental Semantic and Pragmatics in Malik's Muwatta do not stop at the borders of the linguiotic text, but extends to the accompanying one, which includes movements of the human body, such as facial expressions, hands, eyes, head and the legs, mouth and ears. These signify movements represent an important tributary of designation and illustration, meanings and purposes of the speaker in the process of human communication; that affect their behavior dramatically, and translates everything that goes on inside of themselves through the outer parts of the body. The study of accompanying texts  revealed their importance in clarifying precise meamings since they include body movements signals revealed connotations that come in Muwatta  are anger, admiration, sickness, smiling, respect, appreciation, waking, and other meanings that do not appear in the linguistie texts, but appear in context and clues